Interconnectedness and Spillover Effects amongst Stock Markets of the US, China, Germany, Japan and India using DCC-GARCH Model and Diebold Yilmaz Method - Archana Agarwal; Nidhi Dhankhar; Sunita Mehla (Colombo Business Journal)
In a rapidly globalising world, economic boundaries are dissolving as stakeholders seek broader opportunities. Corporations are now multinational, and investors are increasingly turning to global stock markets to maximise gains. Volatility serves as a crucial benchmark, guiding investment decisions in this interconnected landscape. The current study looks at the time-varying spillover effects of the returns of the indices from January 6, 2020, until March 15, 2024, of the five economies of the world, namely, the S&P (United States), SSE (China), Nikkei (Japan), DAX (Germany), and Nifty (India). The conditional correlations and volatility spillovers are measured using the DCC-GARCH model and the Diebold and Yilmaz method. The study concludes that the transmission of information between the indices occurs in the long run except between Germany and China. Further, Germany and the US are net transmitters of volatility spillover, while China, Japan, and India are net receivers. The total spillover among the indices of these five economies is 39.37%.